Case of hepatic portal venous gas in an infant with hypertrophic pyloric stenosis. (5th July 2018) - Daniel, Sherin; Francis, Denease; Tobin, Michelle; Chawla, Anupama
Abstract : Hepatic portal venous gas is the presence of gas within the portal vein and its branches. A 4-week-old male infant presented with 1-week history of non-bloody, non-bilious projectile emesis. Examination was significant for an olive-shaped mass in the abdomen. Bloodwork showed hypokalaemic metabolic alkalosis. Abdominal ultrasound and radiograph was significant for portal venous gas and did not meet radiographic criteria for pyloric stenosis. He underwent upper endoscopy, which showed a narrowed, hypertrophic pylorus. The child underwent pyloromyotomy with resolution of his emesis. Hepatic portal venous gas (HPVG) is very rare and can be seen in the setting of hypertrophic pyloric stenosis. It is believed that an increase in intraluminal dilation and pressure subsequently moves gas from the intestinal mucosa venous system and lymphatics into the portal veins. The presence of HPVG in a well-appearing patient can be benign and should not prompt further testing nor delay treatment.